1982
DOI: 10.1002/ps.2780130212
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Degradation of Picloram

Abstract: The rate of photochemical degradation of aqueous solutions of picloram under ultraviolet light was measured by five different methods of analysis. These were chosen to assay the loss of picloram, dechlorination, alteration or loss of the aromatic amino group, loss of aromaticity, and decarboxylation. The initial rate and mean rate of reaction were determined in each case, and their relationship to each other was used to assess the significance of that particular reaction to the overall degradation of picloram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These peaks disappear within a few hours of electrochemical peroxide treatment and classic Fenton reagent treatment. A photochemical degradation study of picloram (Gear et al, 1982) showed that, in the photolysis of picloram, dechlorination/hydroxylation is the major photochemical process, followed by decarboxylation, loss of aromaticity, and deamination as significant reactions. The mechanisms of degradation in the peroxide systems and in photochemical versions of them will be studied in future work.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks disappear within a few hours of electrochemical peroxide treatment and classic Fenton reagent treatment. A photochemical degradation study of picloram (Gear et al, 1982) showed that, in the photolysis of picloram, dechlorination/hydroxylation is the major photochemical process, followed by decarboxylation, loss of aromaticity, and deamination as significant reactions. The mechanisms of degradation in the peroxide systems and in photochemical versions of them will be studied in future work.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation or removal of PCL from aqueous media has been investigated using different methods ever since the end of the 1960s, with varying degrees of success: photolysis [7][8][9][10][11], photocatalysis [1,[12][13][14], Fenton reaction [15,16], photoFenton reaction [10,17], electro-Fenton reaction [4], chemical oxidation and hydrolysis [11], biosorption [18,19], and biodegradation [20]. As far as we could ascertain, although electrochemical methods have been extensively used for the electrodegradation of organics [21], the degradation of PCL has only been investigated by the electro-Fenton process [4], when 30 mg L -1 PCL solutions were degraded.…”
Section: Introductionmentioning
confidence: 99%
“…There has been recent interest in the use of vegetable oils as replacements for paraffinic oils in emulsifiable spray adjuvants and as carrier solvents for ultralow volume (ULV) herbicide application. These practices should be considered in studies of herbicide photodecomposition, since most reports to date have been on photochemical transformations of herbicides in pure aqueous solution (1,6,8,9,17,21).…”
Section: Introductionmentioning
confidence: 99%